Surveillance and response of hepatitis B virus in Hong Kong Special Administrative Region, 1988–2014 - Lin, Ada Wai-chi; Wong, Ka-Hing (Western Pacific Surveillance and Response, 2016)
The changing epidemiology of hepatitis B in Hong Kong from three-decade commitment in hepatitis B control was reviewed. Yet the disease burden from hepatitis B among adults who had not benefited from the universal neonatal hepatitis B immunization programme needs to be addressed.